Determination of Flavokawain B, in Deprotonized Rat Plasma (After Oral Administration) with an Improved Sensitivity by Capillary Electrophoresis Tandem Mass Spectrometry Detection: It's Application to Pharmacokinetic Study. Issue 2 (3rd March 2020) - Deepakumari, H.N.; Shyla, B; Shruthi, P; Sowmya, P.T; Revanasiddappa, H.D.
Abstract: This article describes a sensitive new capillary zone electrophoresis quadrupole time-of-flight tandem mass spectrometry method for Flavokawain B in rat plasma, which is the novel anti-tumor chemotherapeutic agent. Flavokawain B has been measured in rat plasma after precipitation of plasma proteins by acetonitrile using internal standard carbamzepine. A relatively small aliquot of rat plasma sample was prepared by following a simple one step-deproteinization procedure with 0.2 mL of acetonitrile to a 0.1 mL plasma sample. Separation of flavokawain B from plasma components, fused silica capillary with background electrolyte consisting of 0.25 mM ammonium formate buffer, with sheath liquid (SL) composition of 50:50 methanol and water consisting of 0.25 % of formic acid, pumped at a flow rate of 0.3 nL/min was used and electron spray ionization with positive ion multiple reaction mode was applied for detection of analytes. This new method developed shows the linearity at 0.1-100 ng/mL, and the limit of detection was 0.2819 ng/mL. The precision, accuracy, and stability results were within acceptable ranges. The new method developed and validated CE-MS/MS was successfully applied to intravenous and oral pharmacokinetic studies of flavokawain B in rats.